Peran Dosen untuk Meningkatkan Keterampilan Mahasiswa dalam Praktik Strategi Pembelajaran PAI Berbasis Upload Video di Youtube pada Masa Pandemi Covid-19 - Ning Mukaromah (Center of Education Journal (CEJou), 2022)
The purpose of this study 1) to describe the process of online lectures on the subject model and PAI learning strategies. 2) to describe the role of lecturers in improving student skills in the practice of PAI learning strategies based on uploading videos on youtube. Theresults of the research are as follows: the lecture process on the subject learning model and learning strategy is carried out with a student-centered learning approach. In its application there are 2 kinds of tasks given by lecturers to students, namely group assignments and individual assignments. In research group assignments related to learning models and strategies and individual assignments practicing learning strategies by uploading videos on YouTube by sharing a link on Google Classroom. The role of lecturers to improve learning strategy skills is the lecturer as: 1) motivator, 2) supervisor, and 3) elevator.